Reusable and highly enantioselective water-soluble Ru(II)-Amm-Pheox catalyst for intramolecular cyclopropanation of diazo compounds - Mandour, Hamada S. A.; Nakagawa, Yoko; Tone, Masaya; Inoue, Hayato; Otog, Nansalmaa; Fujisawa, Ikuhide; Chanthamath, Soda; Iwasa, Seiji (Beilstein Journal of Organic Chemistry, 2019)
A reusable and highly enantioselective catalyst for the intramolecular cyclopropanation of various diazo ester and Weinreb amide derivatives was developed. The reactions catalyzed by a water-soluble Ru(II)-Amm-Pheox catalyst proceeded smoothly at room temperature, affording the corresponding bicyclic cyclopropane ring-fused lactones and lactams in high yields (up to 99%) with excellent enantioselectivities (up to 99% ee). After screening of various catalysts, the Ru(II)-Amm-Pheox complex having an ammonium group proved to be crucial for the intramolecular cyclopropanation reaction in a water/ether biphasic medium. The water-soluble catalyst could be reused at least six times with little loss in yield and enantioselectivity.
Keywords: asymmetric synthesis; carbene transfer; cyclopropanation; diazoester; intramolecular diazoamide; Ru(II)-Pheox; water-soluble catalyst; Weinreb amide

(untitled) - Koelle, U. (Coord. Chem. Rev., 1994)

(untitled) - Schaper, L.-A.; Hock, S. J.; Herrmann, W. A.; Kühn, F. E. (Angew. Chem., Int. Ed., 2013)

(untitled) - Martins, L. M. D. R. S.; Pombeiro, A. J. L. (Eur. J. Inorg. Chem., 2016)

(untitled) - Breno, K. L.; Ahmed, T. J.; Pluth, M. D.; Balzarek, C.; Tyler, D. R. (Coord. Chem. Rev., 2006)

(untitled) - Sheldon, R. A. (J. Mol. Catal. A: Chem., 1996)

(untitled) - Darensbourg, D. J.; Joo, F.; Kannisto, M.; Katho, A.; Reibenspies, J. H. (Organometallics, 1992)

(untitled) - Silbestri, G. F.; Flores, J. C.; de Jesús, E. (Organometallics, 2012)

(untitled) - Mohr, F.; Sanz, S.; Tiekink, E. R. T.; Laguna, M. (Organometallics, 2006)

(untitled) - Saoud, M.; Romerosa, A.; Peruzzini, M. (Organometallics, 2000)

(untitled) - Noyori, R. (Angew. Chem., Int. Ed., 2002)

(untitled) - Samec, J. S. M.; Bäckvall, J.-E.; Andersson, P. G.; Brandt, P. (Chem. Soc. Rev., 2006)

Organic Reactions, in Water: Principles, Strategies and Applications - Lindström, U. M. (Blackwell Publishing Ltd., 2007)

(untitled) - Li, C.-J.; Chen, L. (Chem. Soc. Rev., 2006)

Organic Synthesis in Water - Grieco, P. A. (Blackie, 1998)

(untitled) - Li, C. J. (Chem. Rev., 1993)

(untitled) - Lindström, U. M. (Chem. Rev., 2002)

(untitled) - Rideout, D. C.; Breslow, R. (J. Am. Chem. Soc., 1980)

(untitled) - Breslow, R.; Maitra, U.; Rideout, D. (Tetrahedron Lett., 1983)

(untitled) - Breslow, R.; Maitra, U. (Tetrahedron Lett., 1984)

(untitled) - Grieco, P. A.; Garner, P.; He, Z.-m. (Tetrahedron Lett., 1983)

(untitled) - Grieco, P. A.; Yoshida, K.; Garner, P. (J. Org. Chem., 1983)

(untitled) - Barrett, A. G. M.; Braddock, D. C.; Lenoir, I.; Tone, H. (J. Org. Chem., 2001)

(untitled) - Ho, C.-M.; Zhang, J.-L.; Zhou, C.-Y.; Chan, O.-Y.; Yan, J. J.; Zhang, F.-Y.; Huang, J.-S.; Che, C.-M. (J. Am. Chem. Soc., 2010)

(untitled) - Hodgson, D. M.; Chung, Y. K.; Paris, J.-M. (J. Am. Chem. Soc., 2004)

(untitled) - Ikeno, T.; Nishizuka, A.; Sato, M.; Yamada, T. (Synlett, 2001)

(untitled) - Wurz, R. P.; Charette, A. B. (Org. Lett., 2002)

(untitled) - Estevan, F.; Lloret, J.; Sanaú, M.; Úbeda, M. A. (Organometallics, 2006)

(untitled) - Nicolas, I.; Le Maux, P.; Simonneaux, G. (Tetrahedron Lett., 2008)

(untitled) - Abu-Elfotoh, A.-M.; Nguyen, D. P. T.; Chanthamath, S.; Phomkeona, K.; Shibatomi, K.; Iwasa, S. (Adv. Synth. Catal., 2012)

(untitled) - Chanthamath, S.; Iwasa, S. (Acc. Chem. Res., 2016)

(untitled) - Nakagawa, Y.; Nakayama, N.; Goto, H.; Fujisawa, I.; Chanthamath, S.; Shibatomi, K.; Iwasa, S. (Chirality, 2019)

(untitled) - Chanthamath, S.; Mandour, H. S. A.; Tong, T. M. T.; Shibatomi, K.; Iwasa, S. (Chem. Commun., 2016)

(untitled) - Mandour, H. S. A.; Chanthamath, S.; Shibatomi, K.; Iwasa, S. (Adv. Synth. Catal., 2017)

(untitled) - Seitz, M.; Reiser, O. (Curr. Opin. Chem. Biol., 2005)

(untitled) - Collins, I. (J. Chem. Soc., Perkin Trans. 1, 1999)

(untitled) - El Ali, B.; Alper, H. (Synlett, 2000)

(untitled) - Nahm, S.; Weinreb, S. M. (Tetrahedron Lett., 1981)

(untitled) - Vanderwal, C. D.; Vosburg, D. A.; Sorensen, E. J. (Org. Lett., 2001)

(untitled) - Jeong, I. H.; Jeon, S. L.; Min, Y. K.; Kim, B. T. (Tetrahedron Lett., 2002)

(untitled) - Taillier, C.; Bellosta, V.; Meyer, C.; Cossy, J. (Org. Lett., 2004)

(untitled) - Labeeuw, O.; Phansavath, P.; Genêt, J.-P. (Tetrahedron Lett., 2004)

(untitled) - Hisler, K.; Tripoli, R.; Murphy, J. A. (Tetrahedron Lett., 2006)

(untitled) - Friel, D. K.; Snapper, M. L.; Hoveyda, A. H. (J. Am. Chem. Soc., 2008)

(untitled) - Yang, F.; Ackermann, L. (Org. Lett., 2013)

(untitled) - Baker, D. B.; Gallagher, P. T.; Donohoe, T. J. (Tetrahedron, 2013)

(untitled) - Harikrishna, K.; Rakshit, A.; Aidhen, I. S. (Eur. J. Org. Chem., 2013)

(untitled) - Bailey, C. L.; Clary, J. W.; Tansakul, C.; Klabunde, L.; Anderson, C. L.; Joh, A. Y.; Lill, A. T.; Peer, N.; Braslau, R.; Singaram, B. (Tetrahedron Lett., 2015)

(untitled) - Mamuye, A. D.; Castoldi, L.; Azzena, U.; Holzer, W.; Pace, V. (Org. Biomol. Chem., 2015)

(untitled) - Toma, T.; Shimokawa, J.; Fukuyama, T. (Org. Lett., 2007)

(untitled) - Zheng, B.; Hou, S.; Li, Z.; Guo, H.; Zhong, J.; Wang, M. (Tetrahedron: Asymmetry, 2009)